Recurrent Acute Neurogenic Pulmonary Edema after Uncontrolled Seizures - Daniel C. Sacher; Erika J. Yoo (Case Reports in Pulmonology)
Acute pulmonary edema following significant injury to the central nervous system is known as neurogenic pulmonary edema (NPE). Commonly seen after significant neurological trauma, NPE has also been described after seizure. While many pathogenic theories have been proposed, the exact mechanism remains unclear. We present a 31-year-old man who developed recurrent acute NPE on two consecutive admissions after experiencing witnessed generalized tonic-clonic (GTC) seizures. Chest radiographs obtained after seizure during both admissions showed bilateral infiltrates which rapidly resolved within 24 hours. He required intubation on each occasion, was placed on lung protective ventilation, and was successfully extubated within 72 hours. There was no identified source of infection, and no cardiac pathology was thought to be contributory.